2018
DOI: 10.3346/jkms.2018.33.e302
|View full text |Cite
|
Sign up to set email alerts
|

Influences of Tobacco-Related Knowledge on Awareness and Behavior towards Smoking

Abstract: BackgroundA considerable amount of research has shown that knowledge and appropriate awareness are essential for encouraging positive behaviors and promoting health. In Korea, the roles that behavioral changes play in the prevention of cancer have been an important issue since the introduction of the 10 codes for cancer prevention in 2006. Thus, the present study investigated the associations of tobacco-related knowledge with awareness and attitudes towards positive smoking-cessation behaviors.MethodsThe prese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
19
1
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 23 publications
2
19
1
2
Order By: Relevance
“…Similarly, those who believed tobacco use has a positive effect, in making people feel relaxed, were less likely to accept text messaging/WeChat intervention. In earlier studies 32-35 , a higher level of smoking-related knowledge was associated with favorable attitudes towards quitting smoking. We also have found similar findings in the current study.…”
Section: Discussionmentioning
confidence: 73%
“…Similarly, those who believed tobacco use has a positive effect, in making people feel relaxed, were less likely to accept text messaging/WeChat intervention. In earlier studies 32-35 , a higher level of smoking-related knowledge was associated with favorable attitudes towards quitting smoking. We also have found similar findings in the current study.…”
Section: Discussionmentioning
confidence: 73%
“…This finding has also been shown in other health‐promoting processes. For example, tobacco‐related knowledge has been shown to lead to a positive attitude towards smoking cessation, although without necessarily influencing the decision to quit smoking in current smokers (Park et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…The sustainable among these is to raise awareness of the harm of tobacco products. Various scientific researches have been conducted in the literature to raise awareness of tobacco products (Nyman et al 2017, Park et al 2018). However, in our literature review, it has been observed that intervention studies that both create long-term awareness and measure FTND, CO, COHb, and RFT are extremely limited.…”
Section: Discussionmentioning
confidence: 99%